Perivascular Adipocytes Store Norepinephrine by Vesicular Transport. Issue 2 (February 2019) - Ahmad, Maleeha F.; Ferland, David; Ayala-Lopez, Nadia; Contreras, G. Andres; Darios, Emma; Thompson, Janice; Ismail, Alexander; Thelen, Kyan; Moeser, Adam J.; Burnett, Robert; Anantharam, Arun; Watts, Stephanie W.
Abstract : Objective—: Perivascular adipose tissue (PVAT) contains an independent adrenergic system that can take up, metabolize, release, and potentially synthesize the vasoactive catecholamine norepinephrine. Norepinephrine has been detected in PVAT, but the mechanism of its protection within this tissue is unknown. Here, we investigate whether PVAT adipocytes can store norepinephrine using VMAT (vesicular monoamine transporter). Approach and Results—: High-performance liquid chromatography identified norepinephrine in normal male Sprague Dawley rat aortic, superior mesenteric artery, and mesenteric resistance vessel PVATs, and retroperitoneal fat. Real-time polymerase chain reaction revealed VMAT1 and VMAT2 mRNA expression in the adipocytes and stromal vascular fraction of mesenteric resistance vessel PVAT. Immunofluorescence demonstrated the presence of VMAT1 and VMAT2, and the colocalization of VMAT2 with norepinephrine, in the cytoplasm of adipocytes in mesenteric resistance vessel PVAT. A protocol was developed to capture real-time uptake of Mini 202—a functional and fluorescent VMAT probe—in live rat PVAT adipocytes. Mini 202 was taken up by freshly isolated and differentiated adipocytes from mesenteric resistance vessel PVAT and adipocytes from thoracic aortic and superior mesenteric artery PVATs. In adipocytes freshly isolated from mesenteric resistance vessel PVAT, addition of rose bengal (VMAT inhibitor), nisoxetine (norepinephrine transporter inhibitor), or corticosterone (organic cation 3 transporter inhibitor) significantly reduced Mini 202 signal. Immunofluorescence supports that neither VMAT1 nor VMAT2 is present in retroperitoneal adipocytes, suggesting that PVAT adipocytes may be unique in storing norepinephrine. Conclusions—: This study supports a novel function of PVAT adipocytes in storing amines in a VMAT-dependent manner. It provides a foundation for future studies exploring the purpose and mechanisms of norepinephrine storage by PVAT in normal physiology and obesity-related hypertension. Abstract : Supplemental Digital Content is available in the text.